Quantifying the Scandinavian contribution to the vocabulary of Middle English microtoponyms from Wirral and Westmorland - Rye, Eleanor (NORNA-förlaget, 2017)
This article discusses a method that has previously been used to quantify proportions of Scandinavian vocabulary relative to Old English-derived vocabulary in corpora of minor names from areas of Viking-Age Scandinavian settlement in England. This method is then applied to corpora of medieval microtoponyms from two well-known areas of Scandinavian settlement in northwest England, the Wirral peninsula, historically part of the county of Cheshire, and the West Ward of the Barony of Westmorland in the present-day county of Cumbria. The ratio of Scandinavian-derived to Old English-derived place name elements is much higher in the Westmorland corpus than in the Wirral corpus, and this difference is even more marked when the frequency of usage of place-name elements is considered. The higher levels of Scandinavian vocabulary in the Westmorland corpus than in the Wirral corpus are accompanied by greater evidence for the preservation of Scandinavian inflexions. It is impossible to be certain, but there are hints that these discrepancies might be explained by the survival of Scandinavian speech for longer in Westmorland than in Wirral and thus reflect post Conquest developments rather than the circumstances of the initial settlements.